Trustworthiness, Trust, and Immigrants’ Willingness to Call the Police - Bates, Kimberley (Victims & offenders, 2025)
We know that trust in police promotes public willingness to contact the police. We also know that immigrants tend to trust the police less than non-immigrants. In this paper we examine police trustworthiness and immigrants’ trust in police among a sample of immigrants who report being a victim of crime. Specifically, we consider the roles of procedural justice and police effectiveness (i.e. two elements of police trustworthiness) in building immigrants’ trust in police and the subsequent impact this trust has on their willingness to call the police in the future. Drawing on survey data of Vietnamese and Middle Eastern Muslim immigrants in Australia who have been the victim of personal and/or property crimes (N = 355) we find that both measures of police trustworthiness (procedural justice and police effectiveness) are related to immigrants’ willingness to contact the police via the mediating mechanism of trust in police. We also find that results vary depending on victimization type.